375 DIRECT DBS: A Prospective, Multicenter Clinical Trial With Blinding for a Directional Deep Brain Stimulation Lead. (August 2016) - Volkmann, Jens; Chabardes, Stephan; Steinke, G. Karl; Carcieri, Stephen
Abstract : INTRODUCTION: Historically, deep brain stimulation (DBS) systems have delivered stimulation using cylindrical electrodes, which stimulate neurons around the entire circumference of the lead. In this study, we will test a directional DBS lead, which includes radially segmented electrodes designed for selective stimulation in directions orthogonal to the lead trajectory, in addition to standard cylindrical electrodes. Bilateral directional DBS leads will be connected to the Boston Scientific Vercise PC pulse generator, which provides an independent current source for each of its 16 contacts. This system, therefore, is capable of current steering to shape stimulation in the plane orthogonal to the long axis of the lead ("directional stimulation"), as well as providing Ring Mode ("omnidirectional") stimulation equivalent to historical leads. We aim to characterize the effects of directional stimulation in subjects implanted with this system. METHODS: DIRECT DBS is a prospective, randomized, multicenter, double-blind study employing a crossover design. Subjects (10-12, adaptive) will be enrolled per center standard of care. Visits occur in 3 major periods during implant, at 3 months, and at 1 year. Programming is restricted during the first 3 months postimplant to Ring Mode. At 3 months, multiple single-day programming visits will be undertaken to optimize directional programming. Patients are then randomly assigned to 1 of 2 arms (4 weeks per arm) for a double-blind crossover comparison between Ring Mode and unrestricted (eg directional) programming. After the crossover phase, subjects enter an open-label phase of the study, with follow-up at 1 year. RESULTS: This exploratory study will have no prospective statistical hypothesis, but will collect data such as side effect threshold, therapeutic window, Unified Parkinson's Disease Rating Scale (UPDRS) scores, and quantitative accelerometer-based measures of bradykinesia and tremor. CONCLUSION: The DIRECT DBS trial will compare the effects of directional stimulation and omnidirectional stimulation over the first year postimplant. Results will inform future studies.